Peningkatan Kemampuan Perpajakan dalam Pelaporan SPT Masa PPh 21 pada Siswa SMK Negeri Kota Tegal Berdasarkan Undang-Undang HPP - Harjanti, Ririh Sri; Karunia, Anita; Sari, Yeni Priatna; Yunika, Oryza Khilmah; Alfiani, Dwi (Universitas Muhammadiyah Semarang, 2023)
Tax regulations in Indonesia are constantly changing, adapting to changes or dynamics that occur in society. On October 29, 2021, The Act no. 7 /2021 concerning Harmonization of Tax Regulations. which came into effect on January 1, 2022. Therefore, some tax regulations must be adjusted to the HPP law. There are various changes contained in the law, one of which is the renewal of the PPh 21 rate. Education, socialization, understanding and capacity building in the field of taxation need to be carried out from an early age. The younger generation needs to understand the importance of taxes for the state so that later they are expected to be able to protect their own country through tax awareness and taxation capabilities.The purpose of this Community Service activity is to provide education, socialization and increase taxation capabilities related to reporting of SPT Period PPh 21 which is adjusted to the latest regulations, namely The Act No. 7 /2021 for students majoring in Accounting at SMK Negeri 2 Tegal City. The method used in this PKM activity is the lecture method and tutorial or practice of calculating and filling out the SPT Period PPh 21 using the Microsoft Excel application. This activity was carried out at the Accounting Laboratory at SMK Negeri 2 Tegal City. The results of the PKM show that the existence of this PKM activity is able to have an impact on increasing the ability of students to calculate and fill out the SPT Period PPh 21 which has been adjusted to the applicable law.